CAN COMPANY SIZE AND FINANCIAL DISTRESS MODERATE IN SOLVE STOCK RETURNS IN RETAIL SECTOR COMPANIES - Deni Sunaryo; Etty Puji Lestari; Siti Puryandani; Hersugondo Hersugondo (Universitas Kristen Indonesia Toraja, 2022)
This study discusses the effect of Total Asset Turnover (TATO), Price Earning Ratio (PER) and Times Interest Earned Ratio (TIE) to Stock Return with Company Size and Financial Distrsess as a moderating variable . This research uses the object of Retail sub-sector companies in Southeast Asia for the period 2012-2020. The data collected is secondary data with the documentation method in the form of the company's annual report. The sampling method used in this study using purposive sampling technique and obtained 15 companies with a sample of 135 samples. The analysis technique used is Moderated Regression Analysis (MRA), analysis, multiple linear regression, partial test and simultaneous test. The results of the study partially concluded that Total Asset Turnover has no effect on Stock Return, Price Earning Ratio significant effect on Stock Return, and Times Interest Earned Ratio significant effect on Stock Return . The results of the study simultaneously showed that the F-count value was 3.649 and the F-table was 2.70, meaning that the F-count > F-table or a significant value of 0.015 <0.05. So, Total Asset Turnover, Price Earning Ratio and Times Interest Earned Ratio together (simultaneously) have a significant effect on stock return. The results of the study by Moderated Regression Analysis (MRA) concluded that Company Size and Financial Distrsess does not moderate Total Asset Turnover on Stock Return, Company Size and Financial Distrsess does not moderate Price Earning Ratio to Stock Return, and Company Size and Financial Distrsess does not moderate Times Interest Earned Ratio to Stock Return .